Human Adenovirus 36 Infection Increased the Risk of Obesity: A Meta-Analysis Update. Issue 51 (December 2015) - Xu, Mei-Yan; Cao, Bing; Wang, Dong-Fang; Guo, Jing-Hui; Chen, Kai-Li; Shi, Mai; Yin, Jian; Lu, Qing-Bin
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Human adenovirus 36 (HAdV-36), as the key pathogen, was supposed and discussed to be associated with obesity. We searched the references on the association between HAdV-36 infection and obesity with the different epidemiological methods, to explore the relationship with a larger sample size by meta-analysis and compare the differences of epidemiological methods and population subsets by the subgroup analyses. We conducted literature search on the association between HAdV-36 infections and obesity in English or Chinese published up to July 1, 2015. The primary outcome was the HAdV-36 infection rate in the obese and lean groups; the secondary outcomes were the BMI level and BMI z-score in the HAdV-36 positive and negative groups. The pooled odds ratio (OR) was calculated for the primary outcome; the standardized mean differences (SMDs) were calculated for the secondary and third outcomes. Prediction interval (PI) was graphically presented in the forest plot of the random effect meta-analyses. Metaregression analysis and subgroup analysis were performed. Finally 24 references with 10, 191 study subjects were included in the meta-analysis. The obesity subjects were more likely to be infected with HAdV-36 compared to the lean controls (OR = 2.00; 95%CI: 1.46, 2.74; PI: 0.59, 6.76; P  < 0.001) with a high heterogeneity ( I 2  = 80.1%; P  < 0.001) estimated by the random effect model. Subgroup analysis demonstrated that the pooled OR of HAdV-36 infection for obesity were 1.77 (95%CI: 1.19, 2.63; PI: 0.44, 7.03; P  = 0.005) and 2.26 (95%CI: 1.67, 3.07; PI: 1.45, 3.54; P  < 0.001) in the adults and children, respectively. Compared to the HAdV-36 negative subjects, the SMD of BMI was 0.28 (95% CI: 0.08, 0.47; PI: −0.53, 1.08; P  = 0.006) in the HAdV-36 positive subjects with a high heterogeneity ( I 2  = 86.5%; P  < 0.001). The BMI z-score in the children with HAdV-36 infection was higher than those without HAdV-36 infection (SMD = 0.19; 95%CI: −0.31, 0.70; PI: −2.10, 2.49), which had no significantly statistical difference ( P  = 0.453). HAdV-36 infection increased the risk of obesity. HAdV-36 also increased the risk of weight gain in adults, which was not observed in children.